2018
DOI: 10.1515/pjfns-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Improving Storability of Strawberries with Gaseous Chlorine Dioxide in Perforated Clamshell Packaging

Abstract: A chlorine dioxide generating pad has been used as postharvest treatment to maintain the quality and safety of strawberries in two different storage conditions. During the short storage time (3 days at 4°C + 2 days at 20°C) fruit treated with ClO 2 maintained better quality parameters, as color, titratable acidity, total soluble solids, anthocyanins, antioxidant capacity and lower values of weight loss. During the long storage time (12 days at 2°C), the parameters related to postharvest quality were generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Mulberry fruit treated with 60 and 80 mg L −1 ClO 2 for 10-15 min effectively retained flavonoid content after 6 days . Chiabrando et al (2018) reported no significant differences in the total phenolic content of strawberries between ClO 2 gaseous (gas-generating pad) treated and control groups during the short storage period at 4°C. Furthermore, treatment of blueberries with ClO 2 effectively maintained the anthocyanin content of blueberries when stored at 4°C (Chun et al 2013a).…”
Section: Fruitsmentioning
confidence: 89%
See 1 more Smart Citation
“…Mulberry fruit treated with 60 and 80 mg L −1 ClO 2 for 10-15 min effectively retained flavonoid content after 6 days . Chiabrando et al (2018) reported no significant differences in the total phenolic content of strawberries between ClO 2 gaseous (gas-generating pad) treated and control groups during the short storage period at 4°C. Furthermore, treatment of blueberries with ClO 2 effectively maintained the anthocyanin content of blueberries when stored at 4°C (Chun et al 2013a).…”
Section: Fruitsmentioning
confidence: 89%
“…Bleaching is the main cause affecting the color of berries. Chiabrando et al (2018) found that white bleaching was observed on the surface of strawberries treated by ClO 2 after 8 and 12 days of storage at 2°C. also reported that the white damage of mulberries treated for 15 min with 80 mg L −1 ClO 2 was more obvious than after 60 mg L −1 ClO 2 treatment for 15 min, which was similar to the report of .…”
Section: Fruitsmentioning
confidence: 93%
“…It should be noted that the chemical structure of ET and subsequently that of ET metabolites largely depends on the plant source [Landete, 2011;Karlińska et al, 2019]. The main strawberry ET is agrimoniin, a GOG-type dimer composed of two α-1-O-galloyl-2,3:4,6--bis-hexahydroxydiphenoyl-D-glucose units linked by a C-O-C bond between two gallic acid residues [Fotschki et al, 2018;Chiabrando et al, 2018;Nowicka et al, 2019]. The presence of sanguiin H-6 and lambertianin C, but as minor ET, has been also detected in strawberry fruit [Vrhovsek et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…However, high respiration rate, susceptibility to mechanical injury and contamination with fungi and bacteria can reduce their nutritional quality and shelf life considerably (Neri et al 2015). Edible coating (Yan et al 2019), gamma-radiation (Maraei and Elsawy 2017), ultrasound (Cheng et al 2014), ozone, gaseous chlorine dioxide (Chiabrando et al 2018) and modified atmosphere packaging (Matar et al 2018) have been investigated for preserving strawberries. The use of various fungicides is possibly the most commonly used method to control postharvest decay, but these are environmentally unfriendly and some even hazardous to human health (Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%